Climatic variables in Takotsubo cardiomyopathy: role of temperature. Issue 3 (March 2017) - Novo, Giuseppina; Mariano, Enrica; Giambanco, Salvatore; Bonomo, Vito; Manno, Girolamo; Viele, Annalisa; Evola, Salvatore; Giambanco, Francesco; Assennato, Pasquale; Novo, Salvatore; Romeo, Francesco
Abstract : Background: Recent studies documented a seasonal (summer) and circadian (morning) temporal distribution of takotsubo cardiomyopathy (TTC). Aim: The aim of our study was to investigate whether there is a relationship among season, temperature and the occurrence of TTC. A second aim of our study was the comparison of climatic variables in Takotsubo cardiomyopathy versus acute myocardial infarction (AMI). Methods: We enrolled consecutive patients with TTC in three Italian centres and, for comparison consecutive patients with AMI. The frequency of TTC and AMI patients according to month, season and quartiles of temperature (I quartile: 9.8–15°, II quartile: 15–19°, III quartile: 19–25° and IV quartile: 25–38°C) was reported. Climatic variables of TTC and AMI patients were compared. Results: We included in the study 85 patients with TTC and 900 patients with AMI. It was not observed a significant peak in the occurrence of TTC during summer time; however, when compared with AMI, TTC was more frequent in summer. We found an absolute higher frequency of TTC cases with warmer temperatures. TTC cases occurred during warmer temperatures than AMI. Conclusion: Our study does not confirm a summer preference for TTC occurrence, as reported by previous studies, even if, compared with AMI, TTC is more frequent in summer. During warmest days, it was recorded the highest incidence of TTC.